Histopathology of Rabbit Eyelid Laceration Healing With and Without Hyperbaric Oxygen Therapy - Riza, Afdal; Boesoirie, Shanti F.; Caesarya, Sesy; Mardianty, Friska; Rahayu, Putri (Universitas Airlangga, 2026)
Introduction: Effective management of eyelid trauma is essential to promote optimal healing and prevent cicatrix formation. Hyperbaric oxygen therapy (HBOT) has been proposed as an adjuvant treatment that increases oxygen delivery to plasma and tissues, thereby enhancing wound healing. Purpose: This study aimed to compare the histopathological features of wound healing in palpebral lacerations in rabbit models treated with and without HBOT. Methods: Samples meeting the inclusion criteria were included in the study. The HBOT group received 100% oxygen at 2.5 atmospheres absolute (ATA) for 1.5 hours daily over three consecutive days. Both groups received topical fusidic acid. Palpebral tissue samples were collected on day four, followed by hematoxylin-eosin histopathological examination on day five. Parameters assessed included anti-inflammatory cell count, vascularization, and collagen fibril density. Data were analyzed descriptively and through hypothesis testing. Results: It demonstrated that the HBOT group had a significantly higher mean number of anti-inflammatory cells (133.17 ± 11.907) compared to the control group (111.50 ± 17.649; p = 0.032). Vascularization was lower in the HBOT group (11.83 ± 3.00) than in the control group (14.83 ± 3.312), although this difference was not statistically significant (p = 0.114). Collagen fibril density showed no significant difference between groups (p = 0.699). Conclusions: HBOT improved macroscopic wound healing and increased the presence of anti-inflammatory cells. Although differences in collagen density and vascularization were not statistically significant, HBOT showed a favorable trend in enhancing wound healing compared with standard treatment alone.